Reassessing immediate coal phase-out: Dual imperatives of capacity control and renewables expansion in China’s net-zero strategy - Jiaxing Wang; Xi Lu; Hao Wang; Yang Ou; Jianxiao Wang; Dan Tong; Yan Li; Ziwen Ruan; Zihua Yin; Wenlong Zhou; Benjamin McLellan; Emily Xing; et al. (Nexus)
Immediate cessation of investments in new coal-fired power plants is widely regarded as a crucial measure for China to achieve net-zero emission. However, there exists a lack of systematic evaluations regarding the stringent removal of coal power from China’s energy system, raising potential concerns around balancing emission reductions and sustainable transformation. In this study, a comprehensive analysis coupling an integrated assessment model with an hourly power-system optimization model reveals that implementing stringent policies to limit coal-power expansion yields immediate emission-reduction benefit. However, premature and singular capacity control of coal power may hinder the electrification of Chinese society, adversely impacting the adequacy of the power system beyond 2050. These findings underscore the importance of implementing supporting measures when implementing coal-power control policies, including the crucial deployment of renewable energy at a pace significantly exceeding the current rate to achieve complementarity with coal-power control policies. Broader context: Reducing CO2 emissions in power systems is crucial for China in achieving its net-zero emission target. Previous studies have emphasized the broad necessity for immediately stopping new coal-power construction to meet climate targets while largely ignoring the significance of these plants as important safeguards for China’s energy security. A coupled framework illustrates the critical trade-offs China faces between phasing out coal-power and increasing renewable-energy deployment. Implementing stricter coal-power capacity controls, without the lower-cost renewable-energy buffers, will lead to a significant reliance on backstop technologies. The results also indicate the benefits of combining low-cost renewable energy and coal-power control strategies for achieving additional emissions reductions and cost savings, and it is essential to strive for renewable-energy costs decreasing by an additional 14%–34% by 2030 and 55%–59% by 2060 to secure these benefits.